Nutritional strategies to improve post-exercise recovery and subsequent exercise performance - Naderi, A.; Rothschild, J. A.; Santos, H. O.; Hamidvand, A.; Koozehchian, M. S.; Ghazzagh, A.; Berjisian, E.; Podlogar, T. (Sports Medicine, 2025)
Post-exercise recovery strategies influence the body`s ability to restore physiological homeostasis, replenish energy stores, repair muscle damage, and promote desired adaptations, which improve exercise performance. This narrative review examines the impact of nutritional strategies commonly used for enhancing recovery and subsequent exercise performance, particularly when athletes face short recovery periods. Carbohydrate ingestion is essential for glycogen replenishment, especially within the initial hours post-exercise, with its impact dependent on the types, timing, and amount. Protein is essential for accelerating muscle recovery and achieving a positive nitrogen balance, depending on the type and dosage. The co-ingestion of carbohydrates with proteins or fats is explored for its role in maximizing glycogen resynthesis and muscle repair, with evidence supporting the addition of protein to suboptimal carbohydrate intake for enhanced recovery. Moreover, this review addresses the potential benefits of creatine and caffeine co-ingestion for accelerating glycogen synthesis and improving subsequent performance. Hydration strategies, including the use of milk-based beverages and electrolyte solutions, are also discussed, emphasizing their importance in maintaining fluid balance and optimizing recovery. This review also highlights the emerging role of micronutrients such as omega-3 fatty acids, antioxidants, and sodium bicarbonate in reducing muscle damage and improving acid-base balance. Evidence supports the tailored use of these nutritional strategies, particularly for athletes managing tight competition/training schedules. Future research should focus on refining individualized approaches for recovery and investigating the impact of novel supplements on subsequent performance.